Implementation of the Independent Campus in Enhancing Learning Autonomy in Higher Education - Akhyak, Akhyak; Sujianto, Agus; Sahri Sahri (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
The Merdeka Learning - Merdeka Campus (MBKM) policy is a groundbreaking initiative in Indonesia’s higher education system, aiming to create more flexible learning opportunities, connect students with the workforce, and integrate experiential learning. The key strength of this policy lies in its ability to empower students to develop independent learning through extracurricular activities that align with their competencies. At Yudharta Pasuruan University, MBKM has been adopted as an important strategy to enhance the quality of education while preparing graduates to be adaptive and competent in an ever-changing job market. The main aim of this research is to analyze how the planning, implementation, and evaluation of the MBKM program at Yudharta Pasuruan University contribute to improving student independence in learning. The focus of this study includes examining curriculum management, faculty support, and the university's partnerships with external organizations, which are all vital components of the MBKM program. This research uses a qualitative approach, with data collected through interviews, observations, and document analysis. The data analysis process involves data reduction, data presentation, and drawing conclusions. The results of the study indicate that Yudharta Pasuruan University has successfully implemented MBKM through clear policy planning, curriculum adjustments, and the strengthening of external partnerships. Students have gained significant benefits, including increased independence in learning, enhanced critical thinking skills, improved adaptability, and valuable real-world experiences in their chosen fields. These outcomes show that the MBKM program at Yudharta Pasuruan University plays a critical role in transforming higher education, making it more relevant, sustainable, and aligned with the needs of both students and the workforce. This research underscores the importance of MBKM in encouraging the development of a more independent and competent generation of graduates.